The management of anchores companies and their influence on the development of inclusive businesses of the hard yellow corn of the province of Manabi – Ecuador - Sisalema Naranjo, Allan Ramiro (2018)
Objective: To determine the methodological foundations of the Management of Anchor Companies and the Development of Inclusive Businesses. Methods: it is a crosssectional, explanatory quantitative investigation of bibliographic and documentary review, sampling and interviews, surveys, reliability analysis, hypothesis testing and Spearman correlation coefficient. For the processing and analysis of the information, the SPSS.20 software was used. Results: According to our research, the general hypothesis was the existence of a positive influence between the management of anchor companies and the development of inclusive businesses of yellow hard corn in the province of ManabíEcuador. Since an RHO value = 0,893 was generated* with a value p = 0,000 reveals that the hypothesis is true, since the significant relationship between the variable (X) Management of the Anchor Companies and (Y) Development of Inclusive Businesses using the Spearman correlation method was verified. It was obtained as a result that there is a high degree of relationship or significant positive association. Conclusions: we can establish that the research allowed us to link the poorer sections of society to the value chain of the company. This allowed this quintile of the society to become a stakeholder, which allows a link of technology transfer of production and administrative tool guides.